Numerical study of fluid flow across multiple cosmo ball - Hussain, Siti Aslina; Tan, Hong Tat; Idris, Azni (Inderscience Publishers, 2014)
The Cosmo ball mainly has its application as a filter media in an effluent treatment system. A very large surface area could be obtained for microbial attachment as the Cosmo ball has a design such that a surface for fluid interaction with the maximum microbial. This will greatly improve the degradation of organic matter in wastewater through the microbial activities. Cosmo ball is a media used in wastewater treatment in view to increase the surface area of contact and provide longer contact time for biological activities. It is usually placed as a media or as packing in the aeration tank, or in the activated sludge tank. It induces the growth of bacteria on its surface that will serve as a contact area for the wastewater and the microbial. The purpose of this simulation is to analyse the fluid flow pattern namely water around the Cosmo ball. By this means, the overall insights on the interaction of the fluid flow with the Cosmo ball surface can be visualised. The result shows that the fluid flows around the ball disperse inducing mixing in the overall system. There are some retention of flow has been observed that occurs in the ball. The retention of flow induces better microbial interaction to the fluid.